Oral performance and its context - Mackie, C. J. (Mnemosyne, Supplements, 2004)
This volume is concerned with aspects of orality and literacy in the ancient world. It arises from the tremendous contemporary interest among scholars in questions of how literacy and orality co-exist and interact in the ancient world. The contents of the book are refereed papers originally presented at the fifth biennial 'Orality and Literacy in ancient Greece' held at The University of Melbourne in 2002. Papers are offered by scholars from Britain, the USA, Canada and Australia which deal with a range of periods and genres in antiquity, from Homer through to Roman literature. The book will be of great interest to students and scholars of the ancient world.